THE DISTRIBUTION OF COMMERCIAL CROWN ETHER DC18C6 AND THE EXTRACTION STUDY OF ALKALI AND EARTH ALKALI METALS - Bambang Rusdiarso (Indonesian Journal of Chemistry, 2007)
Distribution of A and B isomers of crown-ether DC18C6 on their organic and water phases (chloride, nitrate and sulphocyanide salts) and extraction of alkali and earth alkali metals has been studied. In LiCl 0.1 M environment, lithium extraction could be ignored. The presence of extracted potassium metal may affect the crown ether DC18C6 distribution albeit only a little. In KNO3 0.1 M environment, the distribution coefficient values (d) were 6.1 and 10.3 for A and B isomers, respectively ; while in KCl  0.1 M environment the values were 4.9 and 11.8, respectively. In KSCN 0.1 M, d values for A and B isomers were 40.4 and 36.6, respectively, which were higher than the value obtained from both KNO3 and KCl  0.1 M environments. Caesium metal extraction using DC18C6 occurred weakly, up to only 5%. Strontium extraction using DC18C6 achieved better yield than the caesium extraction. The percentage of extraction increased under organic solvent according to the following: toluene (4%) < chloroform (28%) < TBP (35%).